A Analysis Of Mozila Firefox Software Estimation With COCOMO II - Nurfrianto, Hendy (IJTB (International Journal of Technology And Business), 2019)
In working on a software project, the success of the project must begin with proper planning. If the planning is bad, it will cause project failure. Project failure can be in the form of swelling the cost of the project or project not being completed according to the time specified at the beginning of the plan. Extension of time can result in project cost overruns. To reduce the risk of swelling project costs, the right cost estimation is needed. Estimated project costs are estimates of time and costs including the number of employees working on the project. The cost estimation in this study uses the COCOMO II method. A software is said to be successful if it can be completed in a timely manner. With the appropriate budget and produce software of known quality. Mozila is a browser that is widely used to search for a website but doesn't know much about estimation the cost of making Mozilla therefore using COCOMO II can provide information on how to calculate the estimated cost using COCOMO II and the business of making software in accordance with that method.